Interleukin‐25 Axis Is Involved in the Pathogenesis of Human Primary and Experimental Murine Sjögren's Syndrome. Issue 8 (27th June 2018) - Guggino, Giuliana; Lin, Xiang; Rizzo, Aroldo; Xiao, Fan; Saieva, Laura; Raimondo, Stefania; Di Liberto, Diana; Candore, Giuseppina; Ruscitti, Piero; Cipriani, Paola; Giacomelli, Roberto; Dieli, Francesco; et al.
Abstract : Objective: To investigate the role of the interleukin‐25 (IL‐25)/IL‐17 receptor B (IL‐17RB) axis in experimental Sjögren's syndrome (SS) and in patients with primary SS and primary SS–associated lymphoma. Methods: Expression of IL‐25, IL‐17RB, IL‐17B, and tumor necrosis factor receptor–associated factor 6 (TRAF6) was analyzed on minor salivary gland (SG) samples from patients with primary SS and on parotid gland samples from patients with primary SS–associated B cell non‐Hodgkin's lymphoma (NHL). IL‐17RB expression and the frequencies of natural group 2 innate lymphoid cells (ILC2s), inflammatory ILC2s, and M2‐polarized macrophages were assessed by flow cytometry in SG mononuclear cells and peripheral blood mononuclear cells (PBMCs). Tissue distribution of ILC2s was studied by confocal microscopy. The role of recombinant IL‐25 and of rituximab in modulating IL‐25 expression was investigated in in vitro studies. IL‐25/IL‐17RB and TRAF6 expression and the role of IL‐25 inhibition were also studied in the experimental murine model of SS. Results: Activation of the IL‐25/IL‐17RB/TRAF6 axis correlated with the focus score and was observed in patients with primary SS and in patients with primary SS–associated NHL. A significant increase in the frequency of inflammatory ILC2s was observed both in SG mononuclear cells and in PBMCs. IL‐25 stimulation of isolated SG mononuclear cells and PBMCs from patients and controls resulted both in inflammatory ILC2 expansion and in increased autoantibody production. Rituximab modulated expression of inflammatory ILC2s and IL‐25 in primary SS. SG protein–immunized mice developed overt SS symptoms with increased IL‐25 expression and increased frequency of CD4+IL‐17RB+TRAF6+ cells. IL‐25 neutralization attenuated disease progression and tissue pathology in mice with experimental SS. Conclusion: IL‐25 may promote the inflammatory state in primary SS and may be a potential target for novel disease‐modifying therapeutic strategies in patients with primary SS.